Numerical simulations of shear properties of ice rubble : a shear box experiment - Patil, Aniket; Sand, Björnar; Fransson, Lennart (Luleå tekniska universitet, Byggkonstruktion och -produktion, 2013)
Ice rubble has highly nonlinear behavior and thus simulate shear properties requires sophisticated constitutive models including a relatively large number of parameters and complicated calibration procedures. An attempt has been made to simulate shear properties of ice rubble. A shear box experiment is chosen from test series performed by Fransson and Sandkvist (1985). In this paper a shear box test is simulated with nonlinear finite element code LS-Dyna. A newly implemented material model in LS-Dyna called continuous surface cap model (CSCM) has been used in this simulation. This model is proposed by Schwer and Murray (1994). For the sake of simplicity, experimental results are compared with Mohr-Coulomb material model. A brief overview of continuous surface cap model is given. Finally, comparisons with experimental results have been made. Godkänd; 2013; 20131126 (anipat)